Assessment of Impact of Dirt Bands on Coal Pillar Strength at Different Depths of Cover—A Numerical Simulation Study - SME Annual Meeting 2025 - Abhishek Kumar Singh; Priyadarshi Onam; Sahendra Ram (Society for Mining, Metallurgy & Exploration, 2025)
A numerical simulation study is carried out for assessment of stability of coal pillars having dirt bands by varying its size and depths. Physico-mechanical properties of dirt bands including thickness and its position in pillar system are varied in the simulation study. Results of the simulation study are correlated with the available empirical approaches of pillar strength are validated with field observations. It is observed that the presence of weak dirt bands significantly influences the strength of pillar. An attempt is made to develop correction factor for the available empirical approaches, which are developed without considering the weak dirt bands in pillar system. The findings of the study will be helpful for suitable design of different size of coal pillars at different depths and stages of depillaring operations.